2013
DOI: 10.1002/anie.201209447
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Arynes with Nitrosoarenes—An Approach to Substituted Carbazoles

Abstract: No transition metals are necessary in the reaction of in situ generated arynes with nitrosoarenes to give substituted carbazoles. Depending on the fluoride source and the solvent, either N‐arylated carbazoles or NH‐carbazoles are obtained (see scheme; DME=dimethoxyethane, OTf=trifluoromethanesulfonate). In these cascades a CC and one or two CN bonds are formed. The reactions are easy to conduct and proceed under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(31 citation statements)
references
References 60 publications
1
28
0
2
Order By: Relevance
“…18 The Studer lab disclosed the rapid synthesis of N-substituted carbazoles (13) by reacting arynes with nitrosoarenes. 19 Greaney and coworkers prepared phenoxathiin-dioxides (14) via a thia-Fries/cyclization process. 20 The Kobayashi group reported the formation of isocoumarins (15) via a Pd-catalyzed three-component reaction between arynes, alkynes, and carbon dioxide.…”
Section: Arynes In Heterocycle Synthesismentioning
confidence: 99%
“…18 The Studer lab disclosed the rapid synthesis of N-substituted carbazoles (13) by reacting arynes with nitrosoarenes. 19 Greaney and coworkers prepared phenoxathiin-dioxides (14) via a thia-Fries/cyclization process. 20 The Kobayashi group reported the formation of isocoumarins (15) via a Pd-catalyzed three-component reaction between arynes, alkynes, and carbon dioxide.…”
Section: Arynes In Heterocycle Synthesismentioning
confidence: 99%
“…Very recently, Studer and coworkers developed a conceptually new method for the synthesis of carbazoles using nitrosoarenes and arynes [62]. Depending on the fluoride source and the solvent, either unprotected carbazoles (for CsF in CH 3 CN) or N-arylated carbazoles (for TBAT in DME) were obtained (Scheme 37).…”
Section: Scheme 35mentioning
confidence: 99%
“…[6][7][8] Among them, direct oxidative cyclization reactions have emerged as one of the most powerful approaches for carbazole synthesis because preactivation of the substrates can be avoided, in addition to the atom-and step-economy of the reaction. [9][10][11][12][13] Ever since Åkermark et al reported the oxidative cyclization of diphenylamine via a two C-H bond activation process using a stoichiometric amount of palladium acetate, 14) the palladium-catalyzed intramolecular oxidative coupling reaction of diarylamines in the presence of various oxidants such as cupric acetate, [15][16][17] tert-butyl hydroperoxide, 18) silver oxide, 19) and oxygen [20][21][22] has been further developed and the potential synthetic utility of this type of transformation has been significantly improved (Chart 1A). In recent years, the photochemical cyclization 23,24) and molybdenum pentachloride mediated 25) homogeneous reactions of triarylamines and diarylamines under mild conditions have been successfully developed.…”
Section: Introductionmentioning
confidence: 99%